CSR Objectives and Investor Perceptions in the Islamic Capital Market: An Analysis of Panin Syariah Bank’s Stock Returns - Nur Hidayah Rahim; Syarifuddin Rasyid; Abdul Latief Dollah (Asha Publishing, 2026)
Companies in the financial sector are currently actively carrying out corporate social responsibility (CSR) activities in various fields, such as social, environmental, and religious. These regulations are regulated by the Otoritas Jasa Keuangan (OJK) as a form of responsibility for financial companies to contribute to sustainability. This study examines the impact of Maqashid al-Shariah-based CSR disclosures on stock returns by evaluating company size and leverage as important market signals. Using a quantitative explanatory approach, secondary data were extracted from the annual report and sustainability report of Panin Dubai Syariah Bank for the period 2020–2024. The Maqashid CSR Index was constructed through a content analysis of the five maqashid dimensions, with multiple linear regression applied for comprehensive hypothesis testing. The results show that the Maqashid CSR Index has a significant negative effect on stock returns, indicating that ethical disclosure has not been perceived by the market as a value-enhancing signal. Company size also shows a significant negative impact, while leverage shows a significant positive relationship with returns. These findings imply that the market responds more favourably to an aggressive capital structure than to long-term ethical commitment. This study emphasizes the need to integrate financial and ethical indicators while enhancing investor literacy regarding Maqashid-based CSR to ensure sustainability information effectively supports the ethical long-term investment decision-making process for all key stakeholders.